La collatio lustralis en el régimen fiscal del reino visigodo - del Castillo, Arcadio (Antigüedad y Cristianismo, 1991)
This study is an endeavour to demostrate the fact that the Visigoths did not change the meaning of the tributary system in the Later Roman Empire and therefore the old collatio lustralis, now called solutio auraria weighed upon all those who sold the goods they themselves produced (and probably also those who received a remuneration). The craftsmen and tradesmen of the towns, up to this moment not taxed by the principal tribute of the Visigothic Kingdom (capitatio), were now included in the tributary system.